Papers of Imamu Amiri Baraka - Baraka, Imamu Amiri, 1934-
Two holograph and one typewritten version of an outline for a film proposal based on the life of Charlie Parker. Also includes a letter (26 Nov. 1985) from a Lorimar studio executive rejecting Baraka's film proposal and discussing problems in the proposed project.
Author and social activist. Born Leroy Jones; changed name to LeRoi Jones, and later, to Imamu Amiri Baraka.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Parker, Charlie, -- 1920-1955.; American literature -- African American authors; Jazz musicians; Authors; Social activists